2018
DOI: 10.1038/s41598-018-26768-9
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: The Na/K-ATPase Oxidant Amplification Loop Regulates Aging

Abstract: As aging involves oxidant injury, we examined the role of the recently described Na/K-ATPase oxidant amplification loop (NKAL). First, C57Bl6 old mice were given a western diet to stimulate oxidant injury or pNaKtide to antagonize the NKAL. The western diet accelerated functional and morphological evidence for aging whereas pNaKtide attenuated these changes. Next, human dermal fibroblasts (HDFs) were exposed to different types of oxidant stress in vitro each of which increased expression of senescence markers,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

6
4

Authors

Journals

citations
Cited by 29 publications
(51 citation statements)
references
References 78 publications
1
50
0
Order By: Relevance
“…3T3-L1 pre-adipocytes and MSC-derived adipocytes were plated in 24-well plates and exposed to UTs, IS or p-cresol, with or without subsequent pNaKtide treatment as described above. A Vybrant MTT Cell Proliferation Assay Kit (Invitrogen) was used and manufacturer’s protocol was followed [ 30 ]. The assessment of MTT assay will determine the optimal concentration of UTs that is effective in inducing phenotypic alterations in 3T3-L1 pre-adipocytes, while eliminating the use of possible cytotoxic or ineffective concentrations.…”
Section: Methodsmentioning
confidence: 99%
“…3T3-L1 pre-adipocytes and MSC-derived adipocytes were plated in 24-well plates and exposed to UTs, IS or p-cresol, with or without subsequent pNaKtide treatment as described above. A Vybrant MTT Cell Proliferation Assay Kit (Invitrogen) was used and manufacturer’s protocol was followed [ 30 ]. The assessment of MTT assay will determine the optimal concentration of UTs that is effective in inducing phenotypic alterations in 3T3-L1 pre-adipocytes, while eliminating the use of possible cytotoxic or ineffective concentrations.…”
Section: Methodsmentioning
confidence: 99%
“…Taken together, it indicates that the oxidant amplification loop is important for the development of uremic cardiomyopathy (Figure 2). Moreover, this oxidant amplification loop has also been demonstrated to affect other pathophysiological alterations in other types of animal models including the Western diet, obesity, ageing, steatohepatitis, atherosclerosis, and adipogenesis [113][114][115]. In pre-adipocyte 3T3-L1 cells and MSC-derived adipocytes, uremic toxin indoxyl sulfate and p-cresol sulfate can stimulate the Na/K-ATPase signaling and the oxidant amplification loop [116], suggesting that this oxidant amplification loop is not limited to one cell type.…”
Section: The Na/k-atpase Signaling and Oxidative Stress In Uremic Carmentioning
confidence: 99%
“…The Na/K-ATPase signaling cascade has been extensively studied due to its recently elucidated role as a scaffolding and signaling protein. Studies over the last two decades, since the emergence of the Xie Model of Na/K-ATPase signaling, have demonstrated that activation of this signaling pathway is pivotal in exacerbating oxidative stress in several disease models [8,9,17,18]. While several subunits of Na/K-ATPase have been dissected and known to be involved in its distinct ion pumping function, the α1 subunit of Na/K-ATPase signaling primarily causes its structural modulation leading to the activation of membrane-bound tyrosine kinase protein, Src [19,20].…”
Section: Mechanistic Insights Into Na/k-atpase Oxidant Amplification mentioning
confidence: 99%